Balinese Kulkul Semantic Ontology: REST API Mobile Application Development - Widiatmika, I Putu Agus Wahyu; Adi Pramartha, Cokorda Rai (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 9 No 4 (2021): JELIKU Volume 9 No 4, Mei 2021, 2021)
Kulkul is one of Bali's cultural heritage. Kulkul is used in Balinese society for communication when there is a danger, death, a ritual, and so on. The current phenomenon is that many Balinese people are only able to know and without knowing much knowledge about kulkul. It is because this knowledge is the only word of mouth, making it difficult for it to be collected, stored, retrieved, shared, and renewed. Current technological developments, especially mobile technology, allow the development of mobile applications on cultural knowledge with an ontology approach that will help provide an explicit explanation of this knowledge. In this study, the authors propose the application of a web service with a REST API architecture to help mobile applications integrate Balinese Kulkul Semantic Ontology. This study uses the prototyping method in developing the REST API. From the tests that have been done, it is found that the REST API has successfully received requests and responses which prove that the mobile application is well integrated.